PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 182 PEKANBARU - Ria Mariati; Hendri Marhadi; Syahrilfuddin Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The study was motivated by the lack of student learning achievement with an average value of 57.41. This study aims to improve student learning achievement of IPS for the fourth grade students of Public Alamentary Cchool 182 Pekanbaru with the application of cooperative learning model Numbered Heads Together. Design research is action research (CAR), which was implemented in two cycles. Each cycle consists of two meetings and one-time delivery of materials meeting the daily tests. The research carried out in March and April the number of 41 students consisting of 21 male and 20 female. To be successful class action research, the researchers set the stage that action planning, action, observation and reflection. The data collection instrument of observation and achievement test, data analysis technique that is used as follows, namely Activity Teacher, teacher activities meeting I 50% to the category of Self, Meeting II 62.5% with good category, 83.3% of the IVMeeting of the very good category, 91.6% V Meeting with very good category. Student activities at the meeting of the first meeting of 50% to the category of Self, Meeting II 58.3% with enough categories, 83.3% IV Meeting with excellent category , V Meeting of 95.8% with a very good category. Improved learning outcomes of the student base score is 57.41 increased to 66.34 (15%), the first increase in the Daily Deuteronomy Daily II to 85.24 (48 )% . From this research, the conclusion that by implementing cooperative learning model Numbered Heads Together (NHT) can improve learning outcomes IPS for the fourth grade students of Public Alamentary Cchool 182 Pekanbaru.Key Words: Numbered Heads Together,outcome IPS.